Acceptability of ellagitannin powder as an additive in preparation of sharbet. Issue 6 (14th November 2016) - Kushwaha, Satish Chandra; Kumar, Pradyuman
Abstract : Purpose: The purpose of this study is to look at the application of ellagitannin (ET) powder in sharbet (sugar syrup-based drink) as an additive to produce a polyphenol-enriched drink. ETs are important polyphenols extracted from pomegranate peel (an underutilized juice industry waste). ETs are known for many functional properties such as antioxidative, antibacterial and coloring agent. Naturally, sharbet lacks in polyphenol content; hence, there is a large scope to enhance the functional property of sharbet by addition of ellagitannin powder (ETP) as an additive. Design/methodology/approach: ETP at different concentrations (2, 10, 20, 30, 40 and 50 mg/100 ml sharbet) was applied in plain sharbet (EPS) and lemon-flavored sharbet (ELS). Each concentration of both types of sharbet was analyzed for physicochemical parameters and sensory attributes by sensory panel. Data were analyzed by using statistical tools ( t -test, ANOVA, PCA and graphs) and finding the acceptability of ETP application in sharbet. Findings: Each concentration of both sharbets was analyzed for chemical attributes, i.e. color (L, a, b) ranges (65.81-51.33, −0.24-0.24, −1.57-2.06, respectively), pH (6.30-3.95), titrable acidity as citric acid (0.01-0.1 per cent), total soluble solids (14.7-14.9 per cent), antioxidant activity as DPPH (12.6-71.6 per cent in EPS and 15.5-75.3 per cent in ELS) and sensory analysis (on Hedonic Scale) for sensory attributes, i.e. color, odor, taste and overall acceptability by a sensory panel ( n = 24) of food technologists. Principal component analysis and sensory evaluation score have revealed that sharbet-flavored with lemon extract was liked more in comparison to plain sharbet. ELS containing 30 and 40 mg ETP per 100 ml sharbet was showed to have the highest acceptability index (92.13 and 91.67 per cent) in terms of overall acceptability by sensory panel. It is evident that the addition of ET in polyphenol-deficient beverages could be a market potential toward production of neutraceutical beverages which have antioxidative effects, good taste and are widely accepted. Originality/value: In view of the neutraceutical food development, ETs could be a major polyphenolic component to fulfill the human health requirement. This research can be helpful for commercialization of ETs by the beverage industry.